Religious actors for gender equality - SDG 5: a reflection on the Side by Side Faith Movement for Gender Justice : (policy & practice note) - Thomsen, Jørgen (Religion & development, 2022)
The article reflects on the practical experience of the Side by Side Faith Movement for Gender Justice (SbS): faith actors often play a decisive role in the formation of values, concepts and beliefs that determine how women and men see themselves and each other and how they thus practise gender equality – or not. In both cases, faith actors are key partners in the transformation of ideas and practices towards achieving gender equality – SDG 5. SbS began in 2015 in response to a gradual dominance by restrictive faith actors’ voices in the international debate on gender. Faith-based development agencies and local faith actors already involved in pro-gender-equality practice began building national chapters of SbS to mobilise, organise and strategise our work and have it reflected in international advocacy – including for a change of policy towards improved engagement with religious actors. The article presents this experience in the practical realm of “Community”, whilst the progress made in that realm can only be understood with its intimate link to the realm of “Cosmology”: it is because of what we believe as faith actors that we do what we do. Therefore, interventions for change (Agenda 2030) must be rooted in people’s values, convictions and beliefs if the change is to be sustainable.